Subsidiarity or freedom of association? A perspective from labor law - Bogg, A (Oxford University Press, 2016)
The principle of subsidiarity has long been central to political deliberation about the regulation of work. Historically, it reflected “a tangible concern for the economic rights of workers as they sell their labor on the market.” The activity of work has the potential either to uplift or destroy the human spirit. Where work is “decent work,” the worker can exercise her imagination, initiative and creativity in the workplace. The sphere of work also provides an opportunity for workers to learn the norms of reciprocity and solidarity through trade union participation, with trade unions functioning as vital mediating institutions interposed between the market and the state. Through collective bargaining, workers are empowered to create and shape the norms that regulate their working life. Where work is degrading, consisting of mindless and monotonous tasks and in circumstances of economic deprivation and insecurity, the moral consequences for human beings can be catastrophic. The eclipse of independent trade unionism in contexts of degrading work leads to further disempowerment, anomie, and a loss of collective self-mastery over the terms under which employment is conducted. Such work is an affront to the dignity of human beings, denying workers the opportunity to forge a life for themselves in circumstances of self-respect. Subsidiarity contributes to the promotion of decent work through its identification of the fundamental point of all coordinated human activity, including productive economic activity, which is to enable each human being to participate as fully and actively in living their own life: “anyone who is never more than a cog in big wheels turned by others is denied participation in an important aspect of human well-being.”